Current and emerging therapies for alcohol-associated hepatitis - Francisco Idalsoaga; Gustavo Ayares; Luis Antonio Díaz; Jorge Arnold; María Ayala-Valverde; David Hudson; Marco Arrese; Juan Pablo Arab (Liver Research, 2023)
Alcohol-related liver disease (ALD) encompasses a spectrum of diseases caused by excessive alcohol consumption. ALD includes hepatic steatosis, steatohepatitis, variable degrees of fibrosis, cirrhosis, and alcohol-associated hepatitis (AH), the latter being the most severe acute form of the disease. Severe AH is associated with high mortality (reaching up to 30%–50%) at 90 days. The cornerstone of ALD, and particularly AH, treatment continues to be abstinence, accompanied by support measures such as nutritional supplementation and management of alcohol withdrawal syndrome (AWS). In severe AH with model for end-stage liver disease (MELD) score ≥21, corticosteroids can be used, especially MELD score between 25 and 39, where the highest benefit is achieved. Other key aspects of treatment include the early identification of infections and their associated management and the proper identification of potential candidates for liver transplantation. The development of new therapies based on the pathophysiology and mechanisms of liver injury are underway. This includes the modulation and management of the innate immune response, gut dysbiosis, bacterial translocation, and bacteria-derived products from the intestine. These hold promise for the future of AH treatment.